Improving Sustainable Field-Grown Wheat Production With Azospirillum brasilense Under Tropical Conditions: A Potential Tool for Improving Nitrogen Management - Galindo, Fernando Shintate; Pagliari, Paulo Humberto; Fernandes, Guilherme Carlos; Rodrigues, Willian Lima; Boleta, Eduardo Henrique Marcandalli; Jalal, Arshad; Céu, Elaine Garcia Oliveira; Lima, Bruno Horschut de; Lavres, José; Teixeira Filho, Marcelo Carvalho Minhoto (Frontiers in Environmental Science, 2022)
Sustainable intensification of cropping systems requires to increase productivity and nutrients use efficiency while reducing negative impacts of agricultural management practices on ecosystem and environment. Plant growth-promoting rhizobacteria (PGPR) inoculations are considered one of the most promising and safe strategy to alleviate environmental alterations in context of climatic extremes to improve plant nutrition while reducing dependency of nitrogen (N) fertilizer application. This study investigated the interactive effects of N levels and inoculation with A. brasilense on plant biomass, grain yield, agronomic efficiency (AE) of applied N, apparent N-fertilizer recovery (AFR) and N content in plant targeting economic feasibility of wheat production system. The field trial tested four N application levels applied in side-dressing (control, low, average and high; named 0, 50, 100 and 150 kg N ha-1) and two inoculations (without and with A. brasilense seed inoculation). The results exhibited that inoculation with A. brasilense enhanced AE, AFR and N uptake in wheat plants with increased root and shoot N accumulation and grain N accumulation under average and high N application levels. In addition, inoculation increased root and shoot biomass, leading to a yield increase of 10.3% compared with non-inoculated plants. Wheat plant inoculation associated with application of the average N level provided the greatest profitability. Furthermore, results showed that reducing N fertilization from 100 to 50 kg N ha-1 along A. brasilense inoculation led to an increase in operating profit of 10.5%. In view of low economic cost, ease of application, and high probability of a positive response by wheat crops, even associated with different N application levels, the inoculation with A. brasilense prone to be a key sustainable management practice to improve wheat production under tropical conditions. This practice has the potential to increase wheat grain yield, N use and uptake, and overall farm profitability.